An analysis of the impact of fiscal and monetary policy fluctuations on the disaggregated level renewable energy generation in the G7 countries - Sun, Chuanwang; Khan, Anwar; Liu, Yongzhe; Lei, Ni (Renewable energy, 2022)
The primary aim of sustainable development goals (SDGs) 2030 is to provide a better and more sustainable future for all. Therefore, it is obligatory to focus on all points of SDGs to reach sustainable production and consumption by leaving no point behind. Achieving these goals is impossible if reorientation of fiscal and monetary policies is overlooked, which have substantial policy scope. The current study plans to establish the linkages from monetary and fiscal policies of G7 countries to disaggregated level renewable energy generation between 2000 & 2018. The study adopts the standard Stochastic Impact of Regression on Population, Affluence, and Technology (STIRPAT) model and crossectional augmented econometric algorithms to reach unbiased and efficient conclusions. The empirical results imply that fiscal expansion has a significant positive role in renewable energy generation. At the same time, the expansionary monetary policy indicates a negative response to the investment in renewable energy generation of the G7 countries. The results imply a similar response tendency on the disaggregated levels of energy generation. However, the causal test responds that there is unidirectional causality from renewable energy towards the fiscal and monetary policy indicators of G7 economies. The updated policies are drawn for theory and practice.